Silicon isotopes and the development of the Earth - Savage, P; Paul Savage (2011)
Silicon (Si) isotopes have been extensively studied in low temperature environments but the science of Si isotopes in igneous material has been comparatively ignored. This is because the degree of isotopic fractionation at high temperatures is relatively small, making the accurate measurement of these variations extremely challenging. Using state-of-the-art analytical techniques and instrumentation, which deliver high levels of precision, the objective of this research is to rectify this omission. Specifically, this study aims to investigate whether there are systematic Si isotope variations within, and provide robust Si isotopic compositions for, the major silicate reservoirs on Earth. To this end, a broad range of mantle and crustal lithologies, sourced globally and from various tectonic regimes, have been analysed using high resolution MC-ICP-MS. Analyses indicate that the Si isotopic compositions of mantle-derived mafic and ultramafic material are extremely homogeneous. These data are used to calculate a Bulk Silicate Earth (BSE) average of δ30Si = -0.29 ± 0.08 ‰ (2 s.d.). The degree of Si isotopic fractionation as a result of magmatic differentiation has also been assessed, and found to be small but resolvable between basalt and rhyolitic end-members. Finally, this research shows that, although igneous rocks and sediments derived from the continental crust can be relatively heterogeneous with respect to Si isotopes, bulk averages calculated for the upper, middle and lower continental crust are all very similar to that of BSE. Providing robust estimates for these reservoirs has greatly improved our knowledge of the behaviour of Si isotopes in silicate lithologies and provides a framework for further Si isotopic investigations of such material.